From tandem to catalysis – organic solvent nanofiltration for catalyst separation in the homogeneously W-catalyzed oxidative cleavage of renewable methyl 9,10-dihydroxystearate - Vondran, Johanna; Peters, Marc; Schnettger, Alexander; Sichelschmidt, Christian; Seidensticker, Thomas (Technische Universität Dortmund, 2022)
Feasibility of oxidative cleavage of methyl oleate in a homogeneous reaction, facilitating the subsequent recovery of the catalyst from a single phase, is a challenge. Using the high molecular catalyst phosphotungstic acid (2880 Da) as an affordable catalyst offers potential for membrane separation. To gain insight into side-reactions, the intermediate methyl 9,10-dihydroxystearate was first applied as a model substrate. Thus, the stability of the intermediate methyl 9,10-epoxystearate and the vicinal diol was significantly improved under reaction conditions. Oxidative cleavage of the vicinal diol as a stable intermediate is very promising reaching an overall selectivity of 90% and a selectivity towards the cleavage carboxylic acids of 80%, considering dilution and acidity as the most important parameters. Retention of the catalyst via organic solvent nanofiltration was investigated and we retained 94% of the catalyst in the monophasic system as the first step towards a process concept for a product purification or catalyst recycling strategy.
Catalysis science & technology;12(11)
Keywords: 660